2004
DOI: 10.1007/s10585-004-2153-3
|View full text |Cite
|
Sign up to set email alerts
|

Arg and DAP3 expression was correlated with human thymoma stage

Abstract: Thymoma is one of the most common solid tumors in the mediastinum. As there is no typical cell line for human thymoma, the development and use of molecular-based therapy for thymoma will require detailed molecular genetic analysis of patients' tissues. The recent reports showed that the gain of chromosome 1q regions was frequent in thymoma. We investigated the use of oligonucleotide arrays to monitor in vivo gene expression levels at chromosome 1q regions in the early- (stage I or II) and late-stage (stage IVa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Then hDAP3 may be associated with tumourigenesis and mitochondrial biogenesis through a mechanism of coregulation at the transcriptional level. Our in silico findings are compatible with the published reports concerning the implication of hDAP3 in tumourigenesis or aggressive cellular processes and in the efficacy of mitochondrial translation (Mariani et al, 2001;Sasaki et al, 2004). However, the mechanism of DAP3 gene regulation needs further experimental investigation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Then hDAP3 may be associated with tumourigenesis and mitochondrial biogenesis through a mechanism of coregulation at the transcriptional level. Our in silico findings are compatible with the published reports concerning the implication of hDAP3 in tumourigenesis or aggressive cellular processes and in the efficacy of mitochondrial translation (Mariani et al, 2001;Sasaki et al, 2004). However, the mechanism of DAP3 gene regulation needs further experimental investigation.…”
Section: Discussionsupporting
confidence: 92%
“…First explored in glioblastoma multiform (GBM) cells, the DAP3 mRNA and protein were found to be overexpressed in the invasive GBM cells (Mariani et al, 2001). In thymoma, the DAP3 mRNA level was positively correlated with the stage of the disease defined in the World Health Organisation (WHO) classification (Sasaki et al, 2004). In contrast, a study on senescence induced by oxidative stress in cells showed reduced DAP3 expression (Murata et al, 2006).…”
mentioning
confidence: 98%
“…DAP2 has been reported to be below the limit of detection in 80% of B cell leukemia cell lines, while the frequency of loss of DAP2 expression in breast, bladder and renal carcinoma cell lines ranges from 30 to 40% (16) Promoter hypermethylation of DAP2 was also reported in various types of human tumours, including B cell lymphoma, non-small cell lung, head and neck and colon cancer (17,18). DAP3 was found to be overexpressed in human thyroid oncocytic tumours and correlated with human thymoma stage (19,20). In breast cancer, however, DAP3 was found to be lost in aggressive tumours, and low levels of DAP-3 were found to be linked to a shorter survival of breast cancer patients (20).…”
Section: Discussionmentioning
confidence: 98%
“…25 Most attempts to identify prognostic and predictive biomarkers have focused on correlations with the stage and histological subtype of disease. 9,[26][27][28] The first study to attempt a correlation between gene expression and the risk of development of metastases was reported in 2013. 29 In a retrospective study using archival samples of thymomas from multiple institutions, gene expression levels were used to categorize tumors into two groups based on the probability of developing metastases.…”
Section: Gene Signaturesmentioning
confidence: 99%